2013
DOI: 10.1107/s0907444913018003
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the polypeptide crotamine from the Brazilian rattlesnakeCrotalus durissus terrificus

Abstract: The crystal structure of the myotoxic, cell-penetrating, basic polypeptide crotamine isolated from the venom of Crotalus durissus terrificus has been determined by single-wavelength anomalous dispersion techniques and refined at 1.7 Å resolution. The structure reveals distinct cationic and hydrophobic surface regions that are located on opposite sides of the molecule. This surface-charge distribution indicates its possible mode of interaction with negatively charged phospholipids and other molecular targets to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
1
39
0
5
Order By: Relevance
“…this β -sheet is stabilized by four hydrogen bonds between the strands β 1 and β 3 , (extending from the residues 10–37 and 12–35) and by other two hydrogen bonds between the strands β 2 and β 3 (residues 25–36). However, soon later, other authors described the presence of only two β -sheets [2], which is in accordance with others [3, 4]. Interchain disulfide bonds promote protein cross-linking (Cys 4 –Cys 36 , and Cys 18 –Cys 37 ) between the strand β 3 with the α -helix and the first loop (Pro 13 –Ser 23 ), respectively, while the Cys 11 –Cys 30 bond promotes the connection of β 1 -sheet with the second loop (Gly 26 –Trp 34 ) [1, 4] (Figure 1, Table 1).…”
Section: Introductionsupporting
confidence: 88%
“…this β -sheet is stabilized by four hydrogen bonds between the strands β 1 and β 3 , (extending from the residues 10–37 and 12–35) and by other two hydrogen bonds between the strands β 2 and β 3 (residues 25–36). However, soon later, other authors described the presence of only two β -sheets [2], which is in accordance with others [3, 4]. Interchain disulfide bonds promote protein cross-linking (Cys 4 –Cys 36 , and Cys 18 –Cys 37 ) between the strand β 3 with the α -helix and the first loop (Pro 13 –Ser 23 ), respectively, while the Cys 11 –Cys 30 bond promotes the connection of β 1 -sheet with the second loop (Gly 26 –Trp 34 ) [1, 4] (Figure 1, Table 1).…”
Section: Introductionsupporting
confidence: 88%
“…Recently, it was shown that crotamine selectively inhibits hKv1.1, hKv1.2, and hKv1.3 channels at an IC 50 value of approximately 300 nM, but other K channels are not affected (Peigneur et al, 2012). The structure of crotamine was determined using NMR (Fadel et al, 2005) and X-ray crystallography (Coronado et al, 2013), which revealed three intramolecular disulfide bonds. The overall structure resembles the b-defensin-like superfamily, which is typical for cysteine-stabilized antimicrobial polypeptide (Yount et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although most members of the trans ‐defensin superfamily that have been functionally characterized are antimicrobial, a number of defensin‐like proteins (DLPs) have been recruited to alternative biological functions. Toxic peptides based on this fold are found within the venom of platypus (ovDLP), snakes (eg, crotamine), bearded lizards (eg, helofensin), and sea anemones (eg, APETx2) . The fold has similarly been recruited as enzyme inhibitors in ticks (eg, TCI) and a sea anemone (helianthamide) …”
Section: Introductionmentioning
confidence: 99%